The nature and value of teaching and learning Mandarin Chinese as a school subject in South Africa: a case study of language and literacy ideologies in a public secondary school in South Africa - Reali, Chiara (School of Education, 2026)
In 2014 Mandarin Chinese was officially introduced as a second addi9onal language in South Africa's school curriculum. With China's growing status and influence in the world, South Africa's current posi9oning within the BRICS and South Africa's strong rela9onship with China has raised the importance of research into the landscape of the teaching and learning of Mandarin Chinese as a school subject in South Africa. This case study was conducted in 2021 in South Africa in a public secondary school in which Mandarin Chinese is taught as a school subject within the Confucius Ins9tute project framework. Through linguis9c ethnographic and biographical approaches, this study explores Chinese teachers' and South African students' language and literacy ideologies with respect to Mandarin Chinese and its script. With the “bipar9te nature of ideologies as ‘ontologies plus values'” (Hall & Cunningham, 2020, p. 4) as the main theore9cal principle informing this study, language and literacy ideologies with respect to Mandarin Chinese and its script are explored in rela9on to both “ontologies” and “values” with the aim of showing the deeply intertwined rela9onship between conceptualisa9ons of Mandarin Chinese and of its script and the value aTribu9on to them. The data analysis shows that, despite a 9mid desire shown by a few students for a social approach to language, the teaching and learning of Mandarin Chinese is mainly informed by a conceptualisa9on of Mandarin Chinese as a highly standardised and abstract system which can be packaged and commodified as a well-defined and structured object. As regards the teaching and learning of the Chinese script, some tensions arise. On one hand, the teaching and learning of the Chinese wriTen language seems to be informed by a market-driven skills-based approach, which either over-relies on pinyin (i.e., phone9c system for transcribing Chinese characters into the Roman alphabet) at the expense of the teaching and learning of Chinese characters or conceptualises Chinese characters as arbitrary symbols simply reproducing the spoken language. On the other hand, the teachers also aTempt to convey an approach to Chinese literacy which emphasises the role of Chinese characters within Chinese language and culture, their grapho-seman9c features and their dis9nc9ve rela9onship with spoken language. However, this second approach is not appropriated by the students, who mainly learn Chinese characters as phone9c/arbitrary symbols, thereby poin9ng to a conceptualisa9on of literacy as a decontextualised skill. I argue that both the teaching and learning of Mandarin Chinese as an abstract system of vocabulary and grammar structures and the teaching and learning of the Chinese script as a decontextualised system of phone9c/arbitrary symbols speak of a conceptualisa9on of language and literacy as being exclusively denota9onal, whereby the socio-cultural embeddedness of Mandarin Chinese and of its script are overlooked. Hence, Mandarin Chinese and its script are thought of as “an arbitrary and fungible system of representa9on” (Course, 2018, p. 12), which can be accessed and learnt in the same way as other (alphabe9c) languages. Hence, if languages and their scripts, by virtue of their exclusively denota9onal nature, are conceived as fungible systems of denota9ve communica9on characterised by an ontological equivalence, it follows that they can be easily compared, hierarchised and exchanged according to their instrumental value, namely their high or low likelihood of enabling speakers (and readers/writers) to communicate widely and access opportuni9es. As data shows, Mandarin Chinese is seen, similarly to English, as a highly valuable communica9on tool on a global level, and, thus, as a valuable commodity which can be exchanged for opportuni9es in terms of travelling, acquiring knowledge and accessing well-paid jobs. On the contrary, Afrikaans and African languages, due to their characterisa9on as languages localised into a narrow, economically stagnant and parochial reality, are seen as less valuable because they do not seem to open future opportuni9es for the students. I conclude that a conceptualisa9on of languages and of their scripts in mere denota9onal terms (i.e., languages and scripts as instruments to communicate denota9ve meanings deprived of any socio-cultural connota9on and/or human value) suggests, on one hand, that languages and their scripts are ontologically equivalent (i.e., Mandarin Chinese and its script can be accessed and acquired as any other language); however, on the other hand, the exclusively denota9onal nature of languages and scripts easily allows an aTribu9on of instrumental value to languages and their scripts, which, paradoxically, makes them highly non-equivalent (i.e., Mandarin Chinese and English as more valuable than Afrikaans and African languages within South Africa's linguis9c market). In sum, by embracing the recent ‘ontological turn' in language studies, the explora9on of the intricate rela9onship between ontologies of language (in its spoken and wriTen form) and value aTachment to it might help uncover “highly commodified” (Badwan, 2021, p. 46) understandings of language and literacy in the field of (foreign) language educa9on and invite to think about new and different ways forward. Par9cularly relevant in this project, reflec9ons on the conceptualisa9ons of the nature of literacy informing the teaching and learning of the Chinese script might spark novel thoughts with respect to the teaching of wriTen language in general, especially in terms of its “material culture” (Dickinson, 2017, p. 265), its rela9onship with spoken language and the importance of wri9ng in itself or, in Snoddon's (2022) words, “wri9ng as being” (p. 722).